Character Education Values Analysis on The Chinese Reality Show “Where Are We Going, Dad?” Season Five - Lidwina Nesya Candra; Pamuji, Dian Yuni; Rahmawati, Nailur; Agwinanda, Almira (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
Parents as part of the family which is an informal educational environment are the first and foremost place to develop the foundation of a child's personality and as the foundation of character values in society so that children are able to become people who can internalize good values in their lives both for themselves and for society. The function of education can be disseminated through programs or information that contain teachings about values and ethics. Mass media has several functions, one of which is the function of education. Television as an educational medium can be seen from the educational messages packaged in television programs. Reality shows as a television broadcast program can be used as a medium and model for character education for children. Reality shows often use topics related to everyday reality, making them suitable as character education models for children. The purpose of this research is describe how reality shows “爸爸去哪儿” (Baba qù nǎr, Where Are We Going, Dad?) shows good character components of moral knowledge, moral feeling, and moral action according to Thomas Lickona. The research method used in this research is a qualitative research method with qualitative descriptive type. The data collection technique in this study used observation, note-taking, and documentation techniques. Data analysis techniques in this study were achieved by data condensation, data presentation, and drawing conclusions. On the reality show “爸爸去哪儿” (Baba qù nǎr, Where Are We Going, Dad?), found 40 scenes that show good character components according to Thomas Lickona. From the analysis results, 13 data were found that show components of moral knowledge, 17 data were found that show components of moral feelings, and 10 data were found that show components of moral action.